Analysis of the Application of the Piercing the Corporate Veil Doctrine to Directors and Commissioners Who Concurrently Serve as Shareholders in Third-Party Lawsuits : (Case Study of Decision No. 47/Pdt.G/2021/PN Mtr) - Edgar, Devon; Sunarmi, Sunarmi; Sukarja, Detania (Talenta Publisher, 2024)
A Limited Liability Company (PT) is the most widely used legal entity in Indonesian business practice due to the application of the limited liability principle for shareholders. However, this principle may be misused when directors, commissioners, or shareholders engage in actions that harm third parties. In such circumstances, the piercing the corporate veil doctrine may be invoked to disregard the company’s separate legal personality and impose personal liability on corporate actors. This study examines the application of the piercing the corporate veil doctrine to directors and commissioners who concurrently serve as shareholders in third-party lawsuits, using a normative juridical method and a case study approach on Decision No. 47/Pdt.G/2021/PN Mtr. Although indications of misuse of the corporate entity were present, the court held only the company liable and did not extend liability to the directors or commissioners. The findings indicate that while the doctrine has significant potential to provide legal protection for harmed third parties, its application in Indonesian judicial practice remains limited and is influenced by judicial caution and the high evidentiary threshold required to substantiate abuse of the corporate entity. Therefore, stronger regulatory guidance and more consistent jurisprudence are needed to ensure the doctrine’s effectiveness in delivering justice for aggrieved third parties.